Impact of changing channel length and band gaps of a carbon nanotube on the current of a Carbon Nanotube Field Effect Transistors (CNTFETs) - Bachour, Khoder; Ali, Majdeddin; Alabboud, Ied (Al-Nahrain Journal for Engineering Sciences, 2020)
This paper introduce a new way to simulate the effect of changing the length and the band gap of the nanotube on the current of carbon nanotube field effect transistors (CNTFET( by using simulation tools: FETToy, CNTFET lab, CNT bands 2.0, since this simulation were done in different parameters of ZigZag nanotube. We use three simulations tools because each tool provides simulation of parameters that differ from the parameters of other tools, so we can study more parameters that we change which this article is studied._x000D_ In this paper we studied the effect of changing of ZigZag nanotube length which has a chirality (n,0) on the current of the CNTFET. We have found that the relationship between nanotube length and the current of the CNTFET is an inverse proportional, as the nanotube length increase, the current of CNTFET decrease, and the relation between the band gap of the ZigZag nanotube and current of the CNTFET has been studied too. We have found that this relationship is an inverse proportional, as the band gap increase, the current of CNTFET decrease. Also, we studied the relation between the band gap of the ZigZag nanotube and the average velocity of charges in CNTFET, we found that relationship is an inverse proportional, as the band gap increase, the average velocity of charges of CNTFET decrease.